Logistical And Operational Challenges In Cold Chain Systems For Fishery Products In Developing Countries: A Literature Review: English - Pratama, Andri; Firdaus, Ray Octa (Politeknik Negeri Batam, 2025)
The delivery of fishery products must consistently maintain product quality and integrity to prevent deterioration during the post-harvest period. In developing countries, the distribution of fishery products faces challenges in the post-harvest cold chain system, ranging from infrastructure, technology, and transportation to human resources. This study aimed to identify the logistical and operational challenges in implementing cold chain systems for fishery products in developing countries. The method used in this research is a literature review, with data obtained from accredited journals focused on the topic of cold chain systems. Based on the literature review, it was found that cold chain system challenges in developing countries include road infrastructure that does not connect regions, technology that cannot be applied to the cold chain system because of high financial requirements, transportation units that do not meet cold chain shipping standards, and human resources that lack understanding of the importance of maintaining the quality and integrity of fishery products during the post-harvest period. The implications and recommendations include the need for improved infrastructure development, investment in technology, implementation of transportation units that meet cold chain standards, and enhancement of human resource quality.